CONSTRUCT A STATE OF WELFARE (AN STUDY ON THE IMPROVEMENT OF WELFARE THROUGH THE SOCIAL SECURITY SYSTEM IN INDONESIA) - Dyah Asri Gita Pratiwi; Didit Susiyanto (Politeknik Kesejahteraan Sosial Bandung, 2020)
Poverty is still inherent in every aspect of human life, so it requires comprehensive, integral, and sustainable countermeasures. Indonesia has made a national commitment to eradicate poverty in the context of implementing sustainable development, where the government and all state apparatuses together with various elements of society bear the primary responsibility for achieving sustainable development and simultaneously alleviating poverty. International and national commitments strongly emphasize the importance of social security, especially as a strategy to deal with poverty in a systemic, institutionalized and integrated manner. The development of a social security system program to support the achievement of people's welfare needs to be seen as an effort to restore the community's ability to achieve their own welfare. In Indonesia, the development of a social network system as an alternative to improving people's welfare can be done by revamping the mechanism for implementing a social assistance program that is not centralized, which accommodates the diversity of local characteristics and demands as well as the integration and strong relationship between the management of economic development fields and the field of social welfare. In addition, the social security system needs to be strengthened as an infrastructure of social capital for the community towards a stable life.